La psicología en el saber carolingio : el tema de la mente en Alcuino de York - Peretó Rivas, Rubén (Universidad Nacional de Cuyo. Facultad de Filosofía y Letras. Instituto de Filosofía., 2003)
In this paper the author analyses the concept of the mind in the Alcuin’s treatise De ratione animae. Following the teaching of the Fathers, specially Augustine and Isidore of Sevilla, Alcuin of York comprehends the mind as a nominal part of the soul and as its highest peak, the way in which the man is a God’s image. Finally is presented an sketch of the Alcuin’s knowledge theory as exposed in this treatise.